Clinical insights into nanomedicine and biosafety: advanced therapeutic approaches for common urological cancers - Fattahi, Mohammad Reza; Dehghani, Mansoureh; Paknahad, Somayyeh; Rahiminia, Shafa; Zareie, Deniz; Hoseini, Behzad; Oroomi, Tahmineh Rajaee; Motedayyen, Hossein; Arefnezhad, Reza (Frontiers in Oncology, 2024)
Urological cancers including those of the prostate, bladder, and kidney, are prevalent and often lethal malignancies besides other less common ones like testicular and penile cancers. Current treatments have major limitations like side effects, recurrence, resistance, high costs, and poor quality of life. Nanotechnology offers promising solutions through enhanced diagnostic accuracy, targeted drug delivery, controlled release, and multimodal imaging. This review reflects clinical challenges and nanomedical advances across major urological cancers. In prostate cancer, nanoparticles improve delineation and radiosensitization in radiation therapy, enable fluorescent guidance in surgery, and enhance chemotherapy penetration in metastatic disease. Nanoparticles also overcome bladder permeability barriers to increase the residence time of intravesical therapy and chemotherapy agents. In renal cancer, nanocarriers potentiate tyrosine kinase inhibitors and immunotherapy while gene vectors and zinc oxide nanoparticles demonstrate antiproliferative effects. Across modalities, urological applications of nanomedicine include polymeric, liposomal, and metal nanoparticles for targeted therapy, prodrug delivery, photodynamic therapy, and thermal ablation. Biosafety assessments reveal favorable profiles but clinical translation remains limited, necessitating further trials. In conclusion, nanotechnology holds significant potential for earlier detection, precise intervention, and tailored treatment of urological malignancies, warranting expanded research to transform patient outcomes.